2019
DOI: 10.1155/2019/9013169
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits MMP3 and MMP9 Expression and Secretion by Suppressing TLR4/NF-κB/STAT3 Activation in Ox-LDL-Treated HUVECs

Abstract: Aim. Resveratrol is a natural plant polyphenol. The present study investigated the effects of resveratrol on the Toll-like receptor 4- (TLR4-) mediated expression and secretion of matrix metalloproteinases (MMPs) in oxidized low-density lipoprotein- (ox-LDL-) treated human umbilical vein endothelial cells (HUVECs). Methods. Protein expression was analyzed by immunoblotting. The secretion of MMPs was measured by an enzyme-linked immunosorbent assay. The animal experiments were performed with and without resvera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…MMP3 and MMP9 are extracellular zinc proteases that serve vital roles in the development and progression of atherosclerosis ( 52 ). Zhang et al ( 53 ) reported that resveratrol downregulated MMP3 and MMP9 expression levels in lipopolysaccharide (LPS)-treated human umbilical vein endothelial cells, and reduced LPS-induced MMP3 and MMP9 secretion. The present study indicated that MMP3 and MMP9 expression levels were downregulated by MMP3 knockdown in AngII-treated cells, which suggested that MMP3 knockdown influenced ECM remodeling by regulating MMP3 and MMP9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…MMP3 and MMP9 are extracellular zinc proteases that serve vital roles in the development and progression of atherosclerosis ( 52 ). Zhang et al ( 53 ) reported that resveratrol downregulated MMP3 and MMP9 expression levels in lipopolysaccharide (LPS)-treated human umbilical vein endothelial cells, and reduced LPS-induced MMP3 and MMP9 secretion. The present study indicated that MMP3 and MMP9 expression levels were downregulated by MMP3 knockdown in AngII-treated cells, which suggested that MMP3 knockdown influenced ECM remodeling by regulating MMP3 and MMP9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, we detected the protein level of MMP3, ZO-1, occludin, VE-cadherin, and claudin-5 by Western blot and fluorescence staining. To increase the MMP3 levels, lipopolysaccharide (LPS) in a dose of 100 μ g/mL as a stimulus to increase the MMP3 levels [ 23 , 24 ], and then, the ERK inhibitor FR1080204 [ 25 ] (purchased from Sigma-Aldrich) was administered to investigate the mechanism behind the effects of MMP3 on the BBB.…”
Section: Methodsmentioning
confidence: 99%
“…In general, the mucosal defense against microorganisms can be modulated by increased expression of mucins, tight junctional proteins, secretion of chemokines and cytokines, or release of direct antimicrobials like β-defensins and cathelicidin. We know from other studies that resveratrol affects intracellular signaling pathways, for example, blockage of NFκB activation (Singh et al, 2010), activator protein-1 (Kundu and Surh, 2004), IκBα (Tsai et al, 1999) or TLR4 and STAT3 (Zhang et al, 2019). Notably, a recent study showed the synergistic effect of resveratrol and vitamin D on the heterodimerization of VDR-RXR nuclear factors, which reflected an increase in vitamin D-dependent gene expression involving transactivation by resveratrol (Dampf Stone et al, 2015).…”
Section: Strengthening the Epithelial Barrier For Prevention Of The Lmentioning
confidence: 99%